Adatbázis alkalmazási lehetőségei autoklávos hőkezelésnél - Fabulya, Zoltán; Hampel, György (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The heat treatment of cans, particularly canned meat, is a process with a big energy need. The reduction of the use of the natural resources is the challenge in our days which appears in the new system approach of the environment management, the principle of sustainable development. That is to say, let us produce the same amount of products with less energy consumption, or more amounts with less specific energy consumption. We have to secure the observance of the regulations obtained this way for the sake of the higher quality and the less resource utilization with the use of engineering calculations, modelling and computer simulation. This observance ability is answered with the help of our developed database and model for the computer simulation of heat treatment processes.